Critics, coteries, and Pre-Raphaelite celebrity - Graham, Wendy (Gender and culture, 2017)
Intro -- Table of Contents -- List of Illustrations -- Acknowledgments -- Introduction -- 1. The Pre-Raphaelite Vanguard -- 2. Puff, Slash, Burn: Literary Celebrity -- 3. Fortuneâs Weal -- 4. Dante Gabriel Rossetti: Aesthetic Celebrity -- 5. Anonymous Journalism: The Fleshly School Controversy -- 6. Henry James and British Aestheticism -- Afterword -- Notes -- Works Cited -- Index